ITIL 4 create, deliver and support (CDS) your companion to the ITIL 4 Managing Professional CDS certification - Agutter, Claire (ITGP, 2021)
An excellent supplement to any ITIL 4 Create, Deliver and Support training course ITIL® 4 Create, Deliver and Support (CDS) - Your companion to the ITIL 4 Managing Professional CDS certification is a study guide designed to help students pass the ITIL® 4 Create, Deliver and Support module.
Online resource; title from title details screen (O'Reilly, viewed November 22, 2022)
Keywords: ITIL (Information technology management standard) -- Study guides -- Examinations; Information technology -- Study guides -- Management -- Examinations; Information technology projects -- Study guides -- Management -- Examinations; ITIL (Norme); Examens; Guides de l'étudiant; Technologie de l'information; Gestion; Examens; Guides de l'étudiant; Projets de technologie de l'information; Gestion; Examens; Guides de l'étudiant; examination study guides; Audiobooks; Study guides; Livres audio; Guides de l'étudiant